Evaluating pre-learner driver road safety programmes for Transition Year students in the Republic of Ireland - Ryan, Margaret (School of Psychology, Trinity College Dublin, 2013)
Road traffic crashes (RTCs) impose a considerable burden on society and the risk of crashing is highest among young inexperienced learner and novice drivers, especially males. Research suggests that driving-related knowledge, skills and attitudes begin to develop long before adolescents are old enough to drive. In response, education programmes have been designed which target adolescent pre-learner drivers specifically, with the aim of establishing a solid basis for future driving-related education and subsequent driving behaviour. This thesis consists of nine chapters which serve to describe an evaluation study of pre-learner driver education (PLDE)
Keywords: Behaviour Change; Cognitive Development/Processes; Driver Behaviour; Young male drivers; Education; Transport